Fabrication and surface characterization of titanium dioxide nanotubes on titanium implants - Zheng, Hongming; Xu, Li; Jiao, Yang; Xia, Yan; Wu, Xinglin; Lu, Kaihang; Zhang, Pengpeng; Zhao, Quanming; Zhang, Lu; Ni, Xiaohui (Frontiers in Materials, 2023)
Titanium (Ti) has been widely used in orthopedics and dental implants due to its excellent biocompatibility and mechanical properties. However, the surface of titanium is biologically inert and lacks biological activity, resulting in poor integration between titanium-based implants and surrounding natural bone tissue, which is a common challenge in its clinical application. Surface modification is currently an effective means to improve the biocompatibility and bioactivity of titanium implants. The natural tissues of the human body are assembled from nanomodules, so from a biomimetic perspective, nanostructures should have better biological activity. TiO2 nanotubes (TNTs) have unique physical and chemical properties due to their elastic modulus, large specific surface area, and regular hollow structure similar to those of bone tissue. This study used anodic oxidation technology to prepare TiO2 nanotubes on the surface of titanium. The surface properties of the nanotubes were evaluated using field emission scanning electron microscopy (FE-SEM), X-ray diffraction (XRD), atomic force microscopy (AFM), profilometry, contact angle measurements, etc. The corrosion resistance was tested using an electrochemical workstation. The results indicate that anodic oxidation can be used to successfully prepare titanium dioxide nanotube arrays on the surface of titanium. The nanotubes not only exhibit a good structure but also improve the surface hydrophilicity and corrosion resistance of titanium, thereby demonstrating potential for clinical application.